2007
DOI: 10.1002/elps.200600373
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic coating using methylcellulose and polysorbate 20 for nondenaturing electrophoresis of proteins on plastic microchips

Abstract: A dynamic coating using methylcellulose (MC) and a nonionic detergent (polysorbate 20) was developed, which controlled protein adsorption onto the surface of microchannels on a microchip made of poly(methyl methacrylate) (PMMA). Optimum concentration of polysorbate 20 in combination with the range of MC concentrations controlled the protein adsorption onto the microchannel surface, and increased the solubility of the protein samples while facilitating the injection of high concentrations of MC solutions into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…3, we compared relative mobility of two protein samples BSA (66 kDa) and TI (20 kDa) and a small fluorescent dye (Alexa Fluor 647) in different concentrations of polymers indicated in the figure. We saw that when using MC as the separation media and when the concentration of MC was higher than its entanglement point (0.2%), 18 there was a decrease in mobility; however, until 1% the sieving effect was not yet considerable. We also showed that MC and MC-T in term of suppressing EOF and protein retardation were similar.…”
Section: Eof In Coated Pmma Microchannelsmentioning
confidence: 99%
See 3 more Smart Citations
“…3, we compared relative mobility of two protein samples BSA (66 kDa) and TI (20 kDa) and a small fluorescent dye (Alexa Fluor 647) in different concentrations of polymers indicated in the figure. We saw that when using MC as the separation media and when the concentration of MC was higher than its entanglement point (0.2%), 18 there was a decrease in mobility; however, until 1% the sieving effect was not yet considerable. We also showed that MC and MC-T in term of suppressing EOF and protein retardation were similar.…”
Section: Eof In Coated Pmma Microchannelsmentioning
confidence: 99%
“…In this concentration of polymer solution (0.2%), polymers which we used in this time, PVA, PVP, HPMC, and MC could not entangle with each other. 18,[29][30][31][32] Below entanglement point of polymer solution, the interaction frequency between samples and polymer solutions is important to get a better resolution. In the separation of PVA, the higher EOF which is a counter flow to the electrophoretic mobility increased the separation time and hence, increased the interaction frequency and achieved a better separation of the peaks.…”
Section: Eof In Coated Pmma Microchannelsmentioning
confidence: 99%
See 2 more Smart Citations
“…A hybrid dynamic coating of n-dodecyl b-D-altoside (DDM) and methyl cellulose (MC) method has been developed by Dang et al [10] to suppress analytes adsorption inside a PMMA microchannel. Similarly, Mohamadi et al [11] reported a dynamic coating of methylcellulose (MC) and a nonionic detergent (polysorbate 20) onto PMMA channel also for suppressing the protein adsorption. On the other hand, permanent modification of PMMA surface by surface chemistry, mostly with PEG derivatives, has also been used to reduce the non-specific adsorption of analytes into the PMMA surfaces.…”
Section: Introductionmentioning
confidence: 99%